Kanga: A Skeleton-Based Generic Interface for Parallel Programming - Kist, Deives; Pinto, Bruno; Bazo, Rodrigo; Rauber Du Bois, Andre; Cavalheiro, Gerson Geraldo H. (Proceedings, IEEE 27th International Symposium on Computer Architecture and High Performance Computing Workshops : 18-21 October 2015, Florianópolis, Santa Catarina, Brazil, 2015)
Concurrent programming tools strive to exploit hardware resources as much as possible. Nonetheless, the lack of high level abstraction of such tools often require from the user a reasonable amount of knowledge in order to achieve satisfactory performance requirements as well as they do not prevent error prone situations. In this paper we present Kanga, a framework based on the abstractions of skeletons to provide a generic tool that encapsulate many common parallel patterns. Through two case studies we validate the framework implementation.